DNA fingerprinting of medically important microorganisms by use of PCR. - van Belkum, A (1994)
Selected segments of any DNA molecule can be amplified exponentially by PCR. This technique provides a powerful tool to detect and identify minimal numbers of microorganisms. PCR is applicable both in diagnosis and in epidemiology. By amplification of hypervariable DNA domains, differences can be detected even among closely related strains. PCR fingerprinting is a valuable tool for medical microbiologists, epidemiologists, and microbial taxonomists. The current state of PCR-mediated genotyping is reviewed, and a comparison with conventional molecular typing methods is included. Because of its speed and versatility, PCR fingerprinting will play an important role in microbial genetics, epidemiology, and systematics.